Pengaruh Metode Latihan Bermain Dalam Meningkatkan Teknik Passing Futsal Putri Usia 12-15 Tahun Di Club Abdi Futsal Bekasi - Zulfa, Luthfiyyah; 'Ala, Faridatul; Denatara, Eskar Tri; Pasaribu, Ahmad Muchlisin Natas; Candra, Juli (JURNAL ILMIAH NUSANTARA, 2025)
In order to achieve accurate passing, players need to practice regularly and vary their training, as monotonous training can lead to boredom and hinder the mastery of techniques. A good understanding of passing techniques makes it easier for coaches to implement game strategies. This study aims to determine the effect of playing training methods on improving the passing techniques of 12-15-year-old female futsal players at the Abdi Futsal Club in Bekasi. The research method used was an experimental method with a One-Group Pretest-Posttest Design. The results of this study showed normally distributed and homogeneous data, indicating a significant effect on improving the basic passing techniques of female futsal players at Abdi Futsal Club Bekasi through the playing training method.